PENGARUH CAR, LDR, DAN BOPO TERHADAP RETURN ON ASSETS (ROA) PADA BANK JATIM PERIODE 2019 - 2023 - Moh. Sholeh Asnawi; Putri Novita Sari; Reza Agustin; Riska Dwi Anggarini; Rizky Amelia; Siti A’isyah; Siti Nur Indri Munawarah; Tafiyatul Wulandari (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to analyze the effect of the Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Operating Expenses to Operating Income Ratio (BOPO) on Return On Assets (ROA) at Bank Jatim during the period of 2019-2023. This research employs a quantitative method and secondary data obtained from Bank Jatim's financial statements. The results indicate that partially, CAR (0.418), LDR (0.891), and BOPO (0.224) do not have a significant effect on ROA. The F-test also demonstrates that CAR, LDR, and BOPO simultaneously do not significantly affect ROA, with a significance value of 0.080. Therefore, it can be concluded that changes in CAR, LDR, and BOPO do not have a significant impact on changes in ROA at Bank Jatim during the research period.